2006
DOI: 10.1158/1535-7163.mct-05-0433
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol delivery of urocanic acid–modified chitosan/programmed cell death 4 complex regulated apoptosis, cell cycle, and angiogenesis in lungs of K-ras null mice

Abstract: The low efficiency of conventional therapies in achieving long-term survival of patients with lung cancer calls for development of novel treatment options. Although several genes have been investigated for their antitumor activities through gene delivery, problems surrounding the methods used, such as efficiency, specificity, and toxicity, hinder application of such therapies in clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
61
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 35 publications
7
61
0
Order By: Relevance
“…8,9 Briefly, chitosan was coupled with UA (70 mol %) via an active ester intermediate using 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide hydrochloride (Peptide Institute, Osaka, Japan). The free amino groups of UAC were determined by ninhydrin assay using glucosamine standard, and the composition of UAC was verified by nuclear magnetic resonance spectroscopy (600 MHz, Bruker BioSpin, Munchen, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9 Briefly, chitosan was coupled with UA (70 mol %) via an active ester intermediate using 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide hydrochloride (Peptide Institute, Osaka, Japan). The free amino groups of UAC were determined by ninhydrin assay using glucosamine standard, and the composition of UAC was verified by nuclear magnetic resonance spectroscopy (600 MHz, Bruker BioSpin, Munchen, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…For gene delivery, mice were placed in nose-only exposure chamber and exposed to the aerosol based on the methods used previously. 8,18 For the effects of PTEN against lung cancer development, the K-ras LA1 mice were divided into three groups (three mice per group). Control group was not treated with anything and other two groups were exposed to aerosol containing UAC with PTEN expression vector pcDNA3.0-PTEN (PTEN-treated group) or pcDNA3.0 vector alone (vector control), respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most reports showed that PDCD4 was a pro-apoptosis gene. [27][28][29][30] However, recently a study showed that PDCD4 was an antiapoptotic regulator that inhibited the translation of procaspase-3 mRNA in cells. 31 In our study, there was no significant difference in hepatocyte apoptosis between PDCD4-deficient mice and WT mice at 0 h after LPS/D-GalN injection.…”
Section: Discussionmentioning
confidence: 99%
“…(14) In addition, our previous data showed that aerosol-delivered Pdcd4 regulated lung cancer growth through increasing the cell cycle inhibitors, such as p21 and p27, while suppressing cell proliferation proteins, such as cyclin-dependent kinase 4 and proliferating cell nuclear antigen. (29) p21(Waf1=Cip1) has originally been identified as an inhibitor of G1 cyclin-dependent kinases that mediates the p53-induced growth arrest following DNA damage. (30) In addition, there are several reports showing that p21 (Waf1=Cip1) may also influence cell proliferation in a positive manner.…”
mentioning
confidence: 99%